Design and implementation of Malaysian Microbial Strain Database / Hasdianty Abdullah - Abdullah, Hasdianty (2008)
Malaysian Microbial Strain Database (MMSD) is a database of microorganisms collection from many places in Malaysia. It is developed specially to organize microbial data generated from two projects granted by MOSTI. Relational database modeling has been applied during the design phase in order to organize the microbial data. MMSD is also assisted with graphical user interface (GUI) query and retrieval system to facilitate its users in organizing and regaining the data stored. The system is implemented on three-tier architecture with MySQL as the DBMS at the bottom layer, PHP as server side script in the middle layer and the GUI as the first layer. The relational database system enables three main functions, one is to provide the researchers with web interface to perform data management task for data generated (sampling record, culture information, identified microbes information and 16S rRNA sequence). Secondly, the database system allows the users to issue query to obtain information from the database and third, the system allows users to view results in a user friendly interface.